Dinamika Likuiditas dan Kinerja Keuangan: Bukti Empiris pada PT Telekomunikasi Indonesia Tbk Periode 2021–2024 - Listyawati, Reni; Teguh Erawati; Putri Umbu Tanda; Delon Ringu Langu; Keny Jerikho Kristian Kotto (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to evaluate the financial performance of PT Telekomunikasi Indonesia Tbk (Telkom) through liquidity ratio analysis for the period 2021–2024. Using a quantitative descriptive method, this study measures the company’s ability to meet its short-term obligations during the digital transformation and post-pandemic recovery period. The analysis results show that the average Current Ratio (80.94%) and Quick Ratio (79.55%) are below industry standards, indicating that current assets are not yet fully ideal to guarantee short-term liabilities. However, the average Cash Ratio of 43.56% shows a fairly strong cash position that is close to the standard. The dominance of cash, which accounts for 53.80% of total current assets, provides Telkom with flexibility in maintaining operational stability and funding infrastructure expansion. Overall, although liquidity ratios are below general standards, consistent cash flow indicates that the company’s financial condition is relatively stable and capable of recovering in 2024.